THE STRATEGIC IMPORTANCE OF THE WESTERN HEMISPHERE: DEFI NING U.S. INTERESTS IN THE REGION - R. E. Ellis (Сравнительная политика)
Testimony analyses the emerging importance of Latin America and the Caribbean relative to the security of the United States. Author highlights that relations between the United States and the region of Latin America are related to the USA’s investments and trade as well as to a whole range of problems such as terrorists, crime and refugees. According to the author there are four fundamental challenges in Latin America and the Caribbean: organized crime, Islamic radicalism, Russia and China. The author examines in detail these challenges and analyses their infl uence in the region on the United States. Furthermore, the author stresses that the USA should take necessary measures and develop further strategy to improve the relations with Latin-American countries.